Strength in young rhythmic gymnasts - Batista-Santos, A.; Garganta, R.; Avila-Carvalho, L (Journal of Human Sport & Exercise, 2017)
The aim of this study was: 1) verify if the level of strength in young Portuguese gymnasts change according to competition levels and ranking positions; 2) compare the level of strength in finalists` gymnasts of different competition levels; 3) identify the strength tests that discriminate the gymnasts from the different competition levels. The sample consisted of 68 Portuguese young gymnasts (11.7±0.6 years old) of two different competition levels (Base and 1st division). The International Gymnastics Federation recommended tests for strength assessment were applied. For the statistical analysis, Mann-Whitney and Kruskal-Wallis nonparametric tests, and the discriminant function (forward stepwise) were used. The 1st division presented higher results than the Base gymnasts in all strength tests. Regarding to competition levels by ranking groups, we observed that the finalists in Base level showed higher results than the remaining ranking groups in all strength tests. In 1st division level gymnasts, the finalists achieved higher results only in 66.7% of strength tests than the remaining ranking groups. The finalists in 1st division had higher number of years of training practice in RG and training volume than the finalists in Base level. However, the 1st division gymnasts obtained higher results in 66.7% tests but a superior statistical significance in only one strength test. Lastly, the tests "rope skipping" and "partial trunk elevations" were the strength tests that discriminate the gymnasts groups according to the competitive level.